Peran Perempuan Dalam Pemanfaatan Limbah Perikanan Sebagai Sumber Ekonomi Alternatif Bagi Nelayan Dan Pembudidaya Ikan - Kaunang, Sandra Dewi Elizabet; Santoso, Imam; Yustio, Diaz; Priswanto, Raden Faqih Fadlurrahman; Nurkholipah, Siti (Jurnal Ekonomi Laut dan Air Tawar, 2025)
Fisheries waste is frequently perceived as residue devoid of economic value; however, with appropriate innovation, this waste can be processed into alternative economic resources. This article examines the role of women in utilizing fisheries waste as an economic opportunity capable of enhancing the welfare of fishermen and fish farmers' families. Employing a descriptive qualitative method, this study explores the concepts, strategies, challenges, and solutions regarding fisheries waste processing by women. The findings indicate that women's involvement in innovative fisheries waste processing creates value-added products, generates business opportunities, and strengthens the economic resilience of fishermen and fish farmers' households. Furthermore, the results demonstrate that women play a pivotal role in processing waste into economically valuable products, such as fertilizer, animal feed, and handicrafts, thereby improving family welfare and economic stability.